Peran Beban Kerja dan Komitmen Organisasi terhadap Turnover Pekerja - Farida, Umi; Melinda, Beti (Universitas muhammadiyah palembang, 2019)
Turnover intention is very disruptive to the company's activities in achieving its goals. Among the causes of turnover intention are workload and organizational commitment. The purpose of this study was to determine the role of workload and organizational commitment to turnover intention. The object of this research was PT Agrofarm Nusa Raya Ponorogo workers, with 38 respondents. The nature of causality research with primary data primary data taken through questionnaires. The analytical method used is descriptive analysis and multiple linear regression analysis.The results of this study 1) Workload and organizational commitment play a significant role together towards employee turnover intention 2) Workload has a positive and not significant role on employee turnover intention. 3) Organizational commitment plays a negative and significant role in workers' turnover intention.